2006
DOI: 10.21000/jasmr06021142
|View full text |Cite
|
Sign up to set email alerts
|

Water Migration in Covered Waste Rock, Investigations Using Deuterium as a Tracer

Abstract: Abstract.A deuterium tagged rainfall event with a δD of +213 was applied to the top surface of an experimental covered waste rock pile in May of 2003. The tracer experiment was designed to resolve the spatial variability of infiltrating water and to estimate the magnitude and rate of flow within covered waste rock. The five meter high pile was deconstructed one year later and waste rock was sampled along vertical profiles at 10cm increments. Pore waters were extracted from the waste rock using the centrifugal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Higher evaporation (relative to precipitation) in 2019 occurred likely due to strong evaporation potential and low‐to moderate‐intensity precipitation events. The ratios of net infiltration to precipitation generally fit to the ratios reported in other waste‐rock studies (39% by Carey et al., 2005; 44%–55% by Marcoline, 2008; 37% by Neuner et al., 2013; 42%–69% by Blackmore, 2015).…”
Section: Resultssupporting
confidence: 84%
“…Higher evaporation (relative to precipitation) in 2019 occurred likely due to strong evaporation potential and low‐to moderate‐intensity precipitation events. The ratios of net infiltration to precipitation generally fit to the ratios reported in other waste‐rock studies (39% by Carey et al., 2005; 44%–55% by Marcoline, 2008; 37% by Neuner et al., 2013; 42%–69% by Blackmore, 2015).…”
Section: Resultssupporting
confidence: 84%
“…Although Neuner et al (2013) measured matrixtype flow in a 15 m experimental waste rock pile, they observed wetting front arrivals as high as 1000 times greater than estimated flux rates; Nichol et al (2005), observed wetting front and preferential flow velocities three to four orders of magnitude faster (up to 5 m/day) than the median pore water velocity (1.5 m/year) in the Cluff Lake 10 m experimental pile. The placement of a cover system reduced the preferential flow velocities by 0.1 to 1 m/day with average pore water velocities of 0.39 m/yr to 0.73 m/yr (Marcoline, 2008). Peterson (2014) reported a wide range of velocities for matrix flow (<2 to 12 cm/day), preferential flow (0.4 to 20 m/day), and pressure-induced wetting fronts (7-105 cm/day) in 10 m waste rock piles at Antamina.…”
Section: Matrix Vs Preferential Flow and Immobile Regionsmentioning
confidence: 99%
“…Soil cover systems can be used to reduce water and air infiltration into mine wastes and thereby reduce long-term acid and metal loadings to receiving environments. When properly designed, soil covers can slow down weathering reactions and limit the flushing of stored weathering products (Marcoline et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Reclamation plans for proper capping systems for closure of mine waste impoundments have been established using sensors capable of monitoring water content, rainfall and temperature on site (Lefebvre et al, 2001;Massmann and Farier, 1992;Smolensky et al, 1999;Wels et al, 2003). However, information about water flow and the transport of weathering products through covered mine wastes are still limited even though such information could lead to better ARD prediction methods and refined source control strategies (Marcoline et al, 2006).…”
Section: Introductionmentioning
confidence: 99%